1995
DOI: 10.1007/bf00204147
|View full text |Cite
|
Sign up to set email alerts
|

Embolization of the hepatic falciform artery to prevent supraumbilical skin rash during transcatheter arterial chemoembolization for hepatocellular carcinoma

Abstract: A dilated hepatic falciform artery (HFA) arising from the left hepatic artery was demonstrated on arteriography prior to chemoembolization of an unresectable hepatocellular carcinoma (HCC) located predominantly in the left lobe of the liver. The HFA was occluded by microcoils to prevent a possible toxic supraumbilical skin rash following chemoembolization of the HCC via the left hepatic artery. There were no postprocedure complications. We consider this procedure useful for improving the safety of chemoemboliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 6 publications
0
9
1
Order By: Relevance
“…The frequency reported by Song was higher, which might be caused by larger volume and quicker injection of contrast agent, or by selective angiography of the left hepatic artery. It was reported that chemoembolization of this artery would cause reaction of the umbilical skin [15,17] , which was not observed in our study. We believe that the hepatic falciform artery is a residual artery from the embryo that supplies blood from liver to the umbilical tissues.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The frequency reported by Song was higher, which might be caused by larger volume and quicker injection of contrast agent, or by selective angiography of the left hepatic artery. It was reported that chemoembolization of this artery would cause reaction of the umbilical skin [15,17] , which was not observed in our study. We believe that the hepatic falciform artery is a residual artery from the embryo that supplies blood from liver to the umbilical tissues.…”
Section: Discussioncontrasting
confidence: 80%
“…The frequency identified by angiography is very low, only 2% from literatures [15,16] , until Song reported as 51.6% in a prospective study of angiography. Five cases of hepatic falciform artery were found in our study, all during the angiography of left hepatic artery.…”
Section: Discussionmentioning
confidence: 94%
“…(Fig 10). Some reports have recommended prophylactic embolization of the hepatic falciform artery before TACE to prevent supraumbilical skin and fat necrosis (31,32). Recently, however, Kim et al (33) found no need for prophylactic embolization of the hepatic falciform artery before short-term hepatic arterial chemoinfusion with or without subsequent embolization.…”
Section: Considerations In Nontarget Arteriesmentioning
confidence: 97%
“…Visualization of the HFA occurs in approximately 2% to 13% of hepatic angiograms (2,5). However, visualization of the internal mammary artery (IMA) via the HFA has not been described radiologically before.…”
Section: Discussionmentioning
confidence: 99%